2009
DOI: 10.1182/blood.v114.22.3996.3996
|View full text |Cite
|
Sign up to set email alerts
|

Out of Hospital Treatment of Acute Pulmonary Embolism in Patients with a Low NT-ProBNP Level.

Abstract: 3996 Poster Board III-932 Background NT-proBNP is emerging to be of great importance in risk assessment of patients with acute pulmonary embolism (PE), by identifying both high and low-risk patients. The aim of the present management study was to investigate the safety of out of hospital treatment of patients with acute PE based on a NT-proBNP < 500 pg/ml. Methods Hemodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 0 publications
5
50
0
3
Order By: Relevance
“…Subsequent studies found no significant difference between in-patient and out-patient mortality or recurrent VTE when appropriately selected as 'low risk'. 53,54,56,101 The largest issue remains a lack of standardised criteria for determining low risk patients. A sPESI ≥1 and/or markers of right heart dysfunction should indicate at least intermediate-low risk and encourage admission.…”
Section: Anti-coagulation Guidelinesmentioning
confidence: 99%
“…Subsequent studies found no significant difference between in-patient and out-patient mortality or recurrent VTE when appropriately selected as 'low risk'. 53,54,56,101 The largest issue remains a lack of standardised criteria for determining low risk patients. A sPESI ≥1 and/or markers of right heart dysfunction should indicate at least intermediate-low risk and encourage admission.…”
Section: Anti-coagulation Guidelinesmentioning
confidence: 99%
“…The 3 months overall mortality in these studies ranged from 0% to 43.5%. The percentage of recurrent VTE and major bleeding ranged from 0% to 9.3% and 0% to 3.7%, respectively [8,[10][11][12][13][14][15][16][17][18][19][20].…”
Section: Safety Of Outpatient Treatment 2415mentioning
confidence: 99%
“…Several studies have reported that outpatient management or early discharge of patients with acute PE is safe and effective [8][9][10][11][12][13]. Two systematic reviews suggested that patients with acute PE treated as outpatients had low incidences of major bleeding, recurrent venous thromboembolism (VTE), and mortality [14,15].…”
Section: Introductionmentioning
confidence: 99%